Mouthguard use and cardiopulmonary capacity - A systematic review and meta-analysis - Ferraz Caneppele, T. M.; Borges, A. B.; Masterson Pereira, D.; Almeida Fagundes, A.; Fidalgo, T. K. S.; Maia, L. C. (Sports Medicine International Open, 2017)
This study aimed to perform a systematic review and meta-analysis of the literature to determine the effects of the use of mouthguards (MGs) on cardiopulmonary capacity in athletes (oxygen uptake: VO2 max, and minute ventilation: VE max). Seven electronic databases and reference lists of relevant papers were searched for randomized clinical trials (RCTs) that compared the cardiopulmonary capacity in athletes with and without the use of an MG. The risk of bias tool of the Cochrane Collaboration was used for quality assessment. Fourteen studies were included. For both the overall VO2 max and VE max analyses, significant differences were observed between the MG and no MG conditions, favoring no MG, which presented the highest VO2 max values (p=0.0001; 95% CI; -2.638 to -1.728) and the highest VE max values (p=0.0001; 95% CI; -4.103 to -1.354). When the results were analyzed separately for each subgroup (type of MG and place of use), the meta-analysis showed that the effect of the use of an MG on VO2 max and VE max was not significant when custom-made MGs were used. The use of an MG overall decreased VO2 max and VE max compared to the control. Nevertheless, custom-made MGs seem to have no effect on these parameters.